Democracy in translation : understanding politics in an unfamiliar culture - Schaffer, Frederic Charles (Wilder House series in politics, history, and culture., 1998)
"Frederic C. Schaffer challenges the assumption often made by American scholars that democracy has been achieved in foreign countries when criteria such as free elections are met. Elections, he argues, often have cultural underpinnings that are invisible to outsiders. To examine grass-roots understandings of democratic institutions and political concepts, Schaffer conducted fieldwork in Senegal, a mostly Islamic and agrarian country with a long history of electoral politics. Schaffer discovered that ideas of demokaraasi held by Wolof-speakers often reflect concerns about collective security. Many Senegalese see voting as a matter less of choosing leaders than of reinforcing community ties that may be called upon in times of crisis."--Jacket.